Implikasi Pemberlakuan Sistem Perbankan Ganda Terhadap Penerapan Norma Hukum Islam Di Dalam Perbankan Syariah Di Indonesia - Agus Rojak Samsudin; Hadiat Hadiat (STAI Al-Mas'udiyah, 2024)
The Financial System is regulated in Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (P2SK). Dual banking system is the implementation of the banking system simultaneously, namely conventional banks and Islamic banks simultaneously. The implementation of the Dual banking system is based on Law No. 7 of 1992 concerning Banking, in which it regulates shortcuts about the system and is perfected by Law No. 10 of 1998. As a result of the implementation of the